India - Panagariya, Arvind (Oxford University Press, 2008)
India is not only the world's largest and fiercely independent democracy, but also an emerging economic giant. But to date there has been no comprehensive account of India's remarkable growth or the role policy has played in fueling this expansion. India: The Emerging Giant fills this gap, shedding light on one of the most successful experiments in economic development in modern history